Cervical Cancer Screening Postpandemic: Self-Sampling Opportunities to Accelerate the Elimination of Cervical Cancer - Lozar T; Nagvekar R; Rohrer C; Dube Mandishora RS; Ivanus U; Fitzpatrick MB (Dove Medical Press, 2021)
Taja Lozar,1- 3 Rahul Nagvekar,4 Charles Rohrer,5 Racheal Shamiso Dube Mandishora,6,7 Urska Ivanus,3,8,9 Megan Burke Fitzpatrick1,5 1University of Wisconsin School of Medicine and Public Health, Madison, WI, USA; 2University of Wisconsin Carbone Cancer Center, University of Wisconsin School of Medicine & Public Health, Madison, WI, USA; 3University of Ljubljana, Ljubljana, Slovenia; 4Department of Genetics, Stanford University, Stanford, CA, USA; 5Department of Pathology and Laboratory Medicine, University of Wisconsin School of Medicine and Public Health, Madison, WI, USA; 6University of Zimbabwe College of Health Sciences, Department of Medical Microbiology, Harare, Zimbabwe; 7Early Detection, Prevention and Infections Group, International Agency for Research on Cancer, Lyon, France; 8National Cervical Cancer Screening Programme and Registry ZORA, Epidemiology and Cancer Registry, Institute of Oncology Ljubljana, Ljubljana, Slovenia; 9Association of Slovenian Cancer Societies, Ljubljana, 1000, SloveniaCorrespondence: Megan Burke FitzpatrickUniversity of Wisconsin-Madison School of Medicine and Public Health, MC 8550, 600 Highland Ave, Madison, WI, 53792-8550, USATel +1 608 262-5922Fax +1 608 265-3301Email mbfitzpatric@wisc.eduAbstract: The persisting burden of cervical cancer in underserved populations and low-resource regions worldwide, worsened by the onset of the COVID-19 pandemic, requires proactive strategies and expanded screening options to maintain and improve screening coverage and its effects on incidence and mortality from cervical cancer. Self-sampling as a screening strategy has unique advantages from both a public health and individual patient perspective. Some of the barriers to screening can be mitigated by self-sampling, and resources can be better allocated to patients at the highest risk of developing cervical cancer. This review summarizes the implementation options for self-sampling and associated challenges, evidence in support of self-sampling, the available devices, and opportunities for expansion beyond human papillomavirus testing.Keywords: self-sampling, self-collection, HPV testing, cervical cancer screening, COVID-19